5-Hydroxy-1-tetralone analogues as dual A1/A2A receptor antagonists for the potential treatment of neurological conditions - Janse van Rensburg, H.D. (North-West University, 2018)
Parkinson's disease (PD), a classic movement disorder, is the second most common neurological condition after Alzheimer's disease, with higher incidence and prevalence in advanced age -- consequently, PD patients' quality of life is reduced and, in addition, the disease has a high socio-economic cost. The pharmacological treatment of PD is based on the dopaminergic system and only addresses the motor symptoms of PD and not the non-motor symptoms (such as cognitive deficits and depression) or neurodegeneration. Additionally, L-3,4-dihydroxyphenylalanine (Levo-dopa/L-dopa) is associated with adverse effects such as motor and non-motor fluctuations, dyskinesias and drug-induced psychosis. Therefore, non-dopaminergic treatment that addresses motor and non-motor symptoms, as well as neurodegeneration, is in demand. The manipulation of adenosine receptors (AR's) may be the solution to the PD-conundrum, as an epidemiological study has established an association between the consumption of coffee or caffeine and a reduced risk of developing PD -- caffeine is a xanthine derivative and non-selective A1 and A2A AR antagonist. The present study investigates novel, potent and selective A1 and A2A AR antagonists for the pharmacological treatment of PD. Most A1 and A2A AR antagonists are xanthine and non-xanthine derivatives. The xanthine core forms the basis of numerous potent and selective A1 and A2A AR antagonists, however, these compounds display low water solubility -- limiting their in vivo application. This encouraged the design, synthesis and evaluation of non-xanthine derivatives, generally amino-substituted heterocyclic compounds. Additionally, the less explored N-free heterocyclic ring systems, such as flavonoids (exhibiting wide-ranging biological activity) -- specifically aurones, may be a novel approach to non-xanthine A1 and A2A AR blockade. Structurally related to aurones are benzylidene tetralones, which also possess relatively good A1 and/or A2A AR antagonistic activity and selectivity. Therefore, the current study aimed to gain insight into the importance of structural modifications to ring A and B of the benzylidene tetralone scaffold necessary for A1 and/or A2A AR affinity in order to identify potential drug candidates for PD treatment. Acid catalysed aldol condensation reactions were used to synthesise novel benzylidene tetralones. The synthesised compounds were characterised via nuclear magnetic resonance (NMR) spectrometry, mass spectrometry (MS) and melting points. Furthermore, the purities of these compounds were determined by high performance liquid chromatography (HPLC). The A1 and/or A2A AR affinity of all synthesised compounds were ascertained by means of radioligand binding assays, while GTP shift assays determined selected compounds' functionality as A1 AR agonists or antagonists. It was found that C5-OH substitution on ring A of the benzylidene tetralones in combination with meta (C3')- and/or para (C4')-OH substitution on phenyl ring B of these scaffolds are ideal for A1 and/or A2A AR affinity. Furthermore, substitution of phenyl ring B of the benzylidene tetralones with a 2-aminopyrimidine ring resulting in moderate to high A2A AR affinity. In general, conversion from fused 6- and 5-membered rings (aurones) to fused 6- and 6-membered rings (2-benzylidene-1-tetralones) in combination with ring B substitutions improved A1 and A2A AR affinity. In conclusion, the current study involved the synthesis, characterisation and evaluation of novel 5-substituted 2-benzylidene-1-tetralone analogues to understand the importance of structural modifications to ring A and B of the aurone and 2-benzylidene-1-tetralone scaffold in gaining or even losing A1 and/or A2A AR affinity. The evaluated compounds are promising novel potent and selective A1 and/or A2A AR antagonists and, thus, possible lead compounds for the non-dopaminergic treatment of PD.
MSc (Pharmaceutical Chemistry), North-West University, Potchefstroom Campus
Keywords: Parkinson's disease; adenosine receptors; A1 adenosine receptor antagonists; A2A adenosine receptor antagonists; 2-benzylidene-1-tetralones